ANALISIS KELAYAKAN AGROWISATA (Studi Kasus pada Ghitari Coffee Plantation di Lembang Kaero Kecamatan Sangalla’ Kabupaten Tana Toraja, Provinsi Sulawesi Selatan) - Siama, Astuti; Lanuhu, Nurdin; Diansari, Pipi; Rukmana, Didi; Saadah, Saadah (Jurnal Sosial Ekonomi Pertanian, 2020)
AbstractThe development of coffee plantation land has become an important tourism area in the preservation of agricultural land resources. This study aims to analyze the feasibility of developing agro-tourism in the Ghitari Coffee Plantation in terms of three aspects, namely the biophysical, economic and socio-culture aspects, where if the three aspects are fulfilled then the business is considered feasible to be carried out. This research was carried out at the Ghitari Coffee Plantation, located in Lembang Kaero, Sangalla’ District, Tana Toraja, South Sulawesi. The analytical method used is qualitative and quantitative analysis, where the qualitative analysis is used to analyze the feasibility of biophysical and socio-cultural aspects, while the quantitative analysis is used to analyze economic aspects using the NPV and IRR methods. The results showed that the aspect studied, both from the biophysical, economic and socio-cultural aspect were fulfilled. Based on the results of the calculation of IRR and NPV, the result of PV of Proceeds is Rp. 789,992,946 and PV of Outlays of Rp. 620,000,000, so the NPV value is positive, in the amount of Rp. 169,992,946. While the IRR calculation result is 27%, so it is considered feasible because the IRR value is greater than the interest rate.Keywords:      Business Feasibility Analysis, Coffee Plantation, Agro Tourism.